Productivity Determinants of Islamic Banks in Indonesia: Two-Stage Malmquist Productivity Index - Mutiara Ramadhani Putri; Puji Sucia Sukmaningrum (Universitas Muhammadiyah Malang, 2022)
Islamic Banks in Indonesia experienced a general increase in productivity during the observation period influenced by factors of technological change. This study aims to measure Islamic Banks' productivity level and productivity determinants in Indonesia. This study was quantitatif using Malmquist Productivity Index to measure the level of productivity of Islamic banks. Meanwhile, panel data regression was used to analyze the determinants of productivity. The result foun that Return on Assets (ROA) and Financing to Deposit Ratio (FDR) has significantly affect productivity changes, whole Capital Adequacy Ratio (CAR) has a significant negative effect. The result provides a valuable contribution for consideration regarding managing existing resources to produce optimal output. Bank management can invest in technology and innovation in distributing banking products and services. Islamic bank management also needs to pay attention to the determinants which affect productivity growth.